2014
DOI: 10.1088/0067-0049/215/1/15
|View full text |Cite
|
Sign up to set email alerts
|

Southern Massive Stars at High Angular Resolution: Observational Campaign and Companion Detection

Abstract: Multiplicity is one of the most fundamental observable properties of massive O-type stars and offers a promising way to discriminate between massive star formation theories. Nevertheless, companions at separations between 1 and 100 milli-arcsec (mas) remain mostly unknown due to intrinsic observational limitations. At a typical distance of 2 kpc, this corresponds to projected physical separations of 2-200 AU. The Southern MAssive Stars at High angular resolution survey (smash+) was designed to fill this gap by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
485
4
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 600 publications
(528 citation statements)
references
References 97 publications
33
485
4
6
Order By: Relevance
“…Mason et al (1998) found a possible binary companion at a separation of 0 ′′ . 05, which, however, needs confirmation as it was not seen by Sana et al (2014). Chini et al (2012) classified HD 164438 as SB1, which was recently corroborated by OWN data (Sota et al 2014).…”
Section: Hd 164438mentioning
confidence: 78%
See 2 more Smart Citations
“…Mason et al (1998) found a possible binary companion at a separation of 0 ′′ . 05, which, however, needs confirmation as it was not seen by Sana et al (2014). Chini et al (2012) classified HD 164438 as SB1, which was recently corroborated by OWN data (Sota et al 2014).…”
Section: Hd 164438mentioning
confidence: 78%
“…During an interferometric infrared survey, Sana et al (2014) detected a faint companion separated by 57 mas. This object is not a component of the SB2 system itself because this pair is separated by only 0.07 mas assuming a distance of 1 kpc as suggested by Trepl et al (2012).…”
Section: Hd 164438mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent statistics show that among massive stars this frequency can be as high as 70% (de Mink et al 2013), while it climbs to nearly 100% (Sana et al 2012(Sana et al , 2014 for O-type stars. Chini et al (2012) report that the frequency of binaries is higher than 80% for masses M > 16 M , and it steadily decreases to 20% for masses M ∼ 3 M .…”
Section: Effect Carried By the Presence Of A Binary Componentmentioning
confidence: 99%
“…An alternative scenario that would produce a low binary fraction but that does not invoke variations in the star-formation process may involve runaways stars, which are indeed preferentially single objects (Mason et al 2009;Sana et al 2014). Given that the region is too young to have produced any supernovae, runaways in M 17 should result from dynamical ejection.…”
Section: A Low Binary Fraction?mentioning
confidence: 99%